2007
DOI: 10.1093/jn/137.3.560
|View full text |Cite
|
Sign up to set email alerts
|

Mammary Transcriptome Analysis of Food-Deprived Lactating Goats Highlights Genes Involved in Milk Secretion and Programmed Cell Death ,2

Abstract: Animal nutrition considerably affects milk composition that influences its nutritional quality. Milk component synthesis and secretion by the mammary gland involve expression of a large number of genes whose nutritional regulation remains poorly defined. In this study, we examined the effect of food deprivation (FD) on the expression of 8379 genes in caprine mammary gland using a bovine oligonucleotide microarray. Twelve lactating goats were assigned to 2 groups based on their feeding level (control diet ad li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
78
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 51 publications
16
78
2
2
Order By: Relevance
“…Immediately after death, approximately 50 g of mammary tissue were collected under sterile conditions in the secretory area containing lobulo-alveolar structures (acini), immediately frozen in liquid nitrogen and stored at 2808C. Mammary total RNA was prepared and its quality was checked as previously described (Ollier et al, 2007).…”
Section: Animals and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Immediately after death, approximately 50 g of mammary tissue were collected under sterile conditions in the secretory area containing lobulo-alveolar structures (acini), immediately frozen in liquid nitrogen and stored at 2808C. Mammary total RNA was prepared and its quality was checked as previously described (Ollier et al, 2007).…”
Section: Animals and Managementmentioning
confidence: 99%
“…To supplement these investigations, we undertook gene expression profiling experiments to compare the mammary gland from lactating goats of different CSN1S1 genotypes using a bovine oligonucleotide microarray enlarged to 8379 gene probes. This crosshybridization approach was used due to the lack of caprine microarray, and is previously described (Ollier et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of 161 genes was altered, in particular genes that might be responsible for a slowdown of mammary cell proliferation and differentiation as well as an orientation of mammary cells towards programmed cell death, which could correspond to an early step in mammary gland involution. In addition, genes involved in the drop in milk component secretion were downregulated, such as genes encoding milk proteins and genes involved in lipid metabolism and transport (Ollier et al, 2007). Other examples of genomic results will be indicated in the last section of this paper related to product eating quality.…”
Section: Introductionmentioning
confidence: 92%
“…Nutritional regulation of milk composition Feed deprivation for 2 to 4 days in cows or goats strongly decreased the yields of milk water, lactose, protein and fat; however, only milk lactose concentration decreased (lactose secretion decreased more than water secretion), whereas protein and, more markedly, fat concentrations increased (protein and fat secretion decreased less than water secretion) (Sauvant et al, 1983;Ollier et al, 2007; Table 1). This illustrates the key role of lactose, which is the major component regulating milk osmotic pressure, and the fact that the ability to mobilise some protein and more Nutrients for production and product quality markedly fat reserves make it possible to maintain, at least in the short term, the secretion of other milk components.…”
Section: Implications For Product Qualitymentioning
confidence: 99%
“…An initial study examined The objective is to capture the benefits of the human and bovine genome projects and the 'Livestock Revolution' by: * improving the profitability, productivity, animal welfare and responsible resource use of Australian and global beef businesses * through world-class gene discovery and gene expression research and accelerated adoption of beef industry technologies the response to nutritional intervention in goats. Food deprivation for 48 h alters goat mammary transcriptome simultaneously with milk production and composition (Ollier et al 2007) as shown by the identification of 161 genes responsive to food deprivation, most of which (88%) were downregulated. As expected, genes for milk components were downregulated.…”
Section: Nutrigenomic Studiesmentioning
confidence: 99%